Perancangan Game RPG (Role Playing Game) “Nusantara Darkness Rises” - Roberto Kaban; Fandy Syahputra; Fajrillah Fajrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Games are generally used for entertainment, so by playing games the players will feel happy. Games can also be used as learning media with the concept of learning while playing. Each game has a set of logical functions and rules that guide the course of the game, as well as targets that must be achieved in each level. Each game has different logic and target functions. RPG(Role Playing Game) is one of the most popular game genres. In RPG games, it allows players to take on the roles of multiple imaginary characters and collaborate to complete in-game challenges. This study aims to create a game with the RPG genre with the theme of Indonesian culture and history. The tools used for designing this game are RPG Maker Mv, which is a special software for creating RPG genre games. In the design stage, the author uses the ADDIE method with stages consisting of Analysis, Design, Development, Implementation, and Evaluation. The result of this research is an RPG game entitled